Digital governance, anti-corruption and political stability: An empirical study using cross-national panel data - Yaxing Zhao; Zhizhou Du (PLoS ONE, 2025)
Digital governance has emerged as a critical domain for national development and international cooperation. This study investigates the impact of digital governance on political stability through both theoretical and empirical analyses. First, we establish a theoretical framework to examine the effects of digital governance on political stability and the role that anti-corruption plays in it. Using panel data from 112 countries during 2014–2023, we then examined the quantitative relationship between digital governance and political stability. The results show that digital governance significantly enhances political stability, mediated by anti-corruption efforts. Additionally, the impact of digital governance exhibits heterogeneity across different levels of economic development. Based on these insights, we provide policy recommendations and future research directions to leverage digital governance for enhancing political stability.